PENGARUH ATRIBUT KUALITAS, HARGA, DESAIN DAN PELAYANAN SEPEDA MOTOR HONDA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus Pada PT. ASTRA INTERNASIONAL di MAKASSAR) - Dani Melmambessy, Idayanti Nursyamsi, (Fakultas Ekonomi, UIN Maliki Malang, 2009)
This research aims to find out(1) whether Honda motorbike’s attributes involving quality, price, design, and service simultaneously influence consumers’ purchasing decision at PT. Astra International in Makassar, (2) whether Honda motorbike’s attributes consisting of quality, price, design, and service partially influence consumers’ purcahasing decision at PT.Astra Internatonal in Makassar. The sample consisted of 100 respondents as the users of Honda motorbike in Makassar City. The Data were analyzed using multiple linear regression analysis. The result show that (1)simultaneously, motorbike’s attributes consisting of quality, price, design, and service have a positive and significant influence on consumers’ purchasing decision of Honda motorbike at PT. Astra International in Makassar, (2) partially, quality, price, design, and service attributes have a positive and significant influence on consumers’ purchasing decision of Honda motorbike at PT. Astra International in Makassar.